2006
DOI: 10.1016/j.adolescence.2005.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐taking among adolescents: Associations with social and affective factors

Abstract: The research investigated the associations of social and affective factors with risk‐taking in male and female adolescents. A sample of 269 Israeli adolescents completed questionnaires measuring frequency of involvement in risk‐taking behaviours, relationships with parents, orientation towards peer group, depressive mood, and aggressive behaviour. Correlations and multiple regression analyses showed that risk behaviour among male adolescents was mainly related to orientation towards peer group, while for femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 45 publications
1
62
0
13
Order By: Relevance
“…Caffray and Schneider (2000) concluded that adolescent risk taking could be an attempt to achieve social rewards in order to combat negative feelings caused by poor relationships with parents. However, Michael and Ben-Zur (2007) found that this relationship was moderated by gender and even after adjustment for psychological health, a relationship between family processes and risk behaviours persisted. Furthermore, positive health behaviours such as physical exercise can lead to long and short tem improvements in psychological health (Hallal et al 2006).…”
Section: Risk and Protective Behavioursmentioning
confidence: 64%
See 1 more Smart Citation
“…Caffray and Schneider (2000) concluded that adolescent risk taking could be an attempt to achieve social rewards in order to combat negative feelings caused by poor relationships with parents. However, Michael and Ben-Zur (2007) found that this relationship was moderated by gender and even after adjustment for psychological health, a relationship between family processes and risk behaviours persisted. Furthermore, positive health behaviours such as physical exercise can lead to long and short tem improvements in psychological health (Hallal et al 2006).…”
Section: Risk and Protective Behavioursmentioning
confidence: 64%
“…It is therefore no surprise that aside from the family environment, the social contexts of both school and peers are relevant to a range of health outcomes in adolescence (Settertobulte and Matos 2004;Hurrelmann et al 1996), including mental well-being (Schneider 2000).There are known gender differences in the relative importance of peers and family and the interaction between the two (Michael and Ben-Zur 2007). As with risk and protective health behaviours, analysis of the family environment as a determinant of life satisfaction should therefore adjust for the peer and school contexts to account for any possible confounding.…”
Section: School and Peersmentioning
confidence: 97%
“…is associated with the close relationship with parents (25). On the contrary, there has been great emphasis on the point that adolescents' social orientation is more toward their peers than toward parents (26). The researches show that adolescents with friends involved with high-risk behaviors are more likely to get involved in such behaviors (27,28).…”
Section: Discussionmentioning
confidence: 97%
“…For example, adolescent males' risk-taking is known to be associated with a strong peer orientation (Michael and Ben-Zur 2007), but adolescent females' risk-taking behaviors have been correlated with peer and non-peer relationships such as parental relationship quality (i.e., emotional closeness, communication and mutuality). Thus, a peer-socialization model suggesting that peers are more salient relationships for male adolescents than female adolescents, who are focused on both peer and non-peer relationships, ought to be considered.…”
Section: Adolescent Males' Heightened Susceptibility To Deviant Peer mentioning
confidence: 99%